Analisis Komunikasi Bisnis Pada Layanan Aplikasi Grab Di Kota Kendari - Muhammad Yusuf Sabrin; Hasriani Amin; Sutiyana Fachruddin (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2019)
ABSTRACTThis study aims to describe business communication through Grab Application online services by society of Kendari city. This study uses a qualitative method with research subjects society of Kendari City. Determination technique of informants using snowball sampling. Research informants using the Grab application service criteria. The method of data collecting is done through observation, interviews, literature study and documentation. This study found that business communication through the Grab application online service in the Kendari city uses an online transportation service system as a driver and user of Grab transportation. The Grab application online service makes it easy for users with a practical system for ordering online transportation. Users can understand how to order by determining the destination location and pickup location as seen on the Grab transportation application screen. Users can specify two different destination locations. For Grab drivers, especially Grabbike, it is equipped with safety features in driving, namely the Head Grab Helmets, Grab Jackets and accident insurance. The accident insurance service system is carried out immediately if an accident occurs when using Grab transportation. Payroll system in Grab Application services with the provisions of 20:80 percent. Grab provider companies get 20 percent and 80 percent for Grab drivers from the total income earned by drivers every day of one trip operation. Rewards obtained by Drivers and Grab application users are obtained by activating the reward feature on the Grab account that appears in the Grab application service feature.Keywords: bussines communication, transportation, online service, application, grab